PENGEMBANGAN SISTEM MOBILE JOURNAL BERBASIS ANDROID UNTUK REFERENSI BELAJAR MAHASISWA DI LINGKUNGAN FAKULTAS EKONOMI UNY - Prabowo, Indra Jaya Krisna Gede; Setiawan, Arif; Prakoso, Sabdo Teguh (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
Students have a variety of academic tasks in their study, such as scientific research. Students require a lot of resources in the execution of his duty as a reference. Developments in science and technology is very rapid. Almost everyone has a cell phone. The technology used in mobile phones becomes more advanced. Nowadays mobile phones have emerged and have a variety of operating system that could perform a variety of functions in addition to phone and texting. One of the operating system is the most rapidly growing is Android. Android has an advantage in terms of hardware and software that is open source. So everyone can develop aplication by their own.Based on the above facts the study develops an Android-based application called mobile learning journal as a student reference. Applications can operate online and offline. While online applications are used to locate the journal needed to be downloaded, then can be read offline anytime. The application development through the planning, design, programming, testing. Results of this program is the Android-based applications that can be downloaded and used by anyone. Through testing of various devices stated that Mobiju applications can run properly on all devices.